Benefits Of Neurodevelopment Treatment And Trunk Mobilization In Spastic Diplegi Cerebral Palsy: Case Study - Andayani, Enggal -; Hidayati, Nitaya Putri Nur; -, Sugiono - (Jurnal Fisioterapi Terapan Indonesia, 2024)
ABSTRACT: Background: Spastic diplegia cerebral palsy is a movement disorder with the lower limbs being heavier than the upper limbs which occurs due to brain damage. This disorder makes it difficult for children to carry out functional activities. Neurodevelopmental treatment (NDT) and trunk mobilization are approaches to treating cerebral palsy cases. Objective: To find out the management of neurodevelopmental treatment (NDT) physiotherapy and trunk mobilization in cases of diplegic spastic cerebral palsy. Results: Shortly after the therapy, the results showed a decrease in spasticity, but during subsequent therapy the muscle spasticity returned to normal. For the results of therapy carried out in 5 meetings over 1 month with measurements using the Ashworth scale, the results were T1: 1 and 2 and T5: 1 and 2, functional ability assessment using GMFCS obtained T1 and T5: Level 3, measurement results using GMFM obtained T1 and T5: Dimension A 98%, Dimensions B and C 83.3%, Dimension D 51.2%, Dimension E 5.5%, and the measurement results with XOTR T1 and T5 are T and X. Conclusion: From the results of evaluations carried out using the Ashworth scale, GMFM, GMFCS, and XOTR from T1 to T5 there was no decrease in spasticity, increase in muscle strength or functional ability.